If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.16(x + -12) + 0.33(x + 3) = x + 8 Reorder the terms: -0.16(-12 + x) + 0.33(x + 3) = x + 8 (-12 * -0.16 + x * -0.16) + 0.33(x + 3) = x + 8 (1.92 + -0.16x) + 0.33(x + 3) = x + 8 Reorder the terms: 1.92 + -0.16x + 0.33(3 + x) = x + 8 1.92 + -0.16x + (3 * 0.33 + x * 0.33) = x + 8 1.92 + -0.16x + (0.99 + 0.33x) = x + 8 Reorder the terms: 1.92 + 0.99 + -0.16x + 0.33x = x + 8 Combine like terms: 1.92 + 0.99 = 2.91 2.91 + -0.16x + 0.33x = x + 8 Combine like terms: -0.16x + 0.33x = 0.17x 2.91 + 0.17x = x + 8 Reorder the terms: 2.91 + 0.17x = 8 + x Solving 2.91 + 0.17x = 8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2.91 + 0.17x + -1x = 8 + x + -1x Combine like terms: 0.17x + -1x = -0.83x 2.91 + -0.83x = 8 + x + -1x Combine like terms: x + -1x = 0 2.91 + -0.83x = 8 + 0 2.91 + -0.83x = 8 Add '-2.91' to each side of the equation. 2.91 + -2.91 + -0.83x = 8 + -2.91 Combine like terms: 2.91 + -2.91 = 0.00 0.00 + -0.83x = 8 + -2.91 -0.83x = 8 + -2.91 Combine like terms: 8 + -2.91 = 5.09 -0.83x = 5.09 Divide each side by '-0.83'. x = -6.13253012 Simplifying x = -6.13253012
| 5g+9=2g+3 | | (1/2)x-(3/5)y=5 | | -10y=68-2(4-2y) | | 2x^5+6x^3+4x=0 | | 16p^6q^4+32p^5q^3-48pq^2= | | -x^3+9x+2=0 | | -3(6s+2)= | | r^2+7r-18= | | -2(2y-1)+2y=4(y+4) | | -2(u+2)=7u-1+3(3u+1) | | -.16(x-12)+.5(x+2)=x-1 | | 3(9x-8)=2(4x+2) | | 72x-89=x-81 | | (2*4y)+(2*5y)=0 | | (3z+2)(4-z)=0 | | 15+10x=13x | | 10(X)=X-7 | | 4(8n-3)+7n= | | G-2/7=6 | | 4(r+1)= | | 0=-5x^2+3x^2 | | 4+4(3x-2)=-2(4x-6)+8x | | 4+4(3x-2)=-2(4x-6) | | 0=-5x^2+3x^2ln(x) | | 2x*2x-3=9 | | 21+3y-3=12y-12-4y | | -3.5w+0.1=0.2w-3.6 | | a^2=-12a | | 9+ln(20x)=17-2ln(x) | | 6y+3=4y+11 | | -6(-3w+6)-3w=6(w-2)-9 | | 2k^2+12k-70=-2 |